Numerical investigation of the near-field flow-structures produced by a pitched and skewed vortex generating jet. - Jewkes, James; Chung, Y. (University of Ottawa, 2011)
A large-eddy simulation of a velocity-ratio (VR = 1:0), pitched and skewed vortex generating jet issuing into a turbulent boundary layer (Red = 2000) is presented. As the jet issues from the orifice, an asymmetrical counter-rotating vortex pair is produced, consisting of a strong primary vortex and a weaker secondary vortex. The secondary vortex quickly dissipates to leave the primary vortex, which persists farther downstream. The primary vortex replaces the near-wall region with higher momentum fluid, and is shown to be associated with improved skin friction downstream of the jet. This increase in skin friction has been previously shown to be associated with improved resistance to boundary-layer separation.